2000
DOI: 10.1046/j.1471-4159.2000.0751997.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of α7 Nicotinic Acetylcholine Receptors in Activation of Tyrosine Hydroxylase and Dopamine β‐Hydroxylase Gene Expression in PC12 Cells

Abstract: Nicotine treatment increases intracellular free Ca 2ϩ concentration [Ca 2ϩ ] i , stimulates catecholamine release, and elevates gene expression for the catecholamine biosynthetic enzymes tyrosine hydroxylase (TH) and dopamine ␤-hydroxylase (DBH). However, the type of nicotinic acetylcholine receptors (nAChRs) mediating these events is unclear. The nAChR receptor antagonists ␣-bungarotoxin (␣BTX) and methyllycaconitine greatly reduced the nicotine-triggered initial transient rise in [Ca 2ϩ ] i and prevented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 53 publications
(75 reference statements)
2
46
2
Order By: Relevance
“…There are three types of cytoplasmic calcium signals initiated by neuronal nAChR activation; (1) direct calcium influx through the nAChR [6,11] , (2) indirect calcium influx through voltage-dependent calcium channels (VDCCs) which are activated by the nAChR-mediated depolarization [6,11] , and (3) calcium-induced calcium release (CICR) (triggered by the two sources listed above) from the endoplasmic reticulum (ER) through the ryanodine receptors [12][13][14] and inositol (1,4,5)-triphosphate receptors (IP 3 Rs) [13][14][15] .…”
Section: Cytoplasmic Calcium Signals Initiated By Neuronal Nachr Actimentioning
confidence: 99%
See 2 more Smart Citations
“…There are three types of cytoplasmic calcium signals initiated by neuronal nAChR activation; (1) direct calcium influx through the nAChR [6,11] , (2) indirect calcium influx through voltage-dependent calcium channels (VDCCs) which are activated by the nAChR-mediated depolarization [6,11] , and (3) calcium-induced calcium release (CICR) (triggered by the two sources listed above) from the endoplasmic reticulum (ER) through the ryanodine receptors [12][13][14] and inositol (1,4,5)-triphosphate receptors (IP 3 Rs) [13][14][15] .…”
Section: Cytoplasmic Calcium Signals Initiated By Neuronal Nachr Actimentioning
confidence: 99%
“…The involvement of IP 3 R-dependent calcium stores in neuronal nAChR signaling was shown when nAChRinduced calcium responses were reduced with IP 3 R-selective antagonists [13][14][15] . The functional interaction between IP 3 and ryanodine receptor-dependent calcium signals is considered to be a key signaling mechanism [28] .…”
Section: Cytoplasmic Calcium Signals Initiated By Neuronal Nachr Actimentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinic transmission can also influence gene expression as originally shown for immediate early genes and genes involved in transmitter synthesis (Chalazonitis and Zigmond, 1980;Greenberg et al, 1986;Pelto-Huikko et al, 1995;Salminen et al, 1999;Gueorguiev et al, 2000). The underlying mechanisms have been examined in some detail in the chick ciliary ganglion .…”
Section: Long-term Consequencesmentioning
confidence: 99%
“…Previously, we found that the ␣7 nAChR subtype is required for the nicotine-elicited elevation of TH mRNA in PC12 cells. Moreover, ␣7 receptor agonists were at least as effective as nicotine in triggering these effects (Gueorguiev et al, 2000). The ␣7 subunits can form a homopentameric receptor, which is reported to desensitize rapidly compared with other nAChR subtypes.…”
mentioning
confidence: 99%